2017
DOI: 10.1016/j.bbadis.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of spinal metabolites underlying α-Me-5-HT-evoked pruritus compared with histamine and capsaicin assessed by proton nuclear magnetic resonance spectroscopy

Abstract: The mechanism behind itching is not well understood. Proton nuclear magnetic resonance (H-NMR) spectroscopic analysis of spinal cord extracts provides a quick modality for evaluating the specific metabolic activity of α-Me-5-HT-evoked pruritus mice. In the current study, four groups of young adult male C57Bl/6 mice were investigated; one group treated with saline, while the other groups intradermally injected with α-Me-5-HT (histamine independent pruritogen), histamine (histamine dependent pruritogen) and caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…All pruritic behaviors were evaluated as previously described with minor modifications [ 6 , 43 , 44 ]. The tests of algogenic behavior by capsaicin were performed similar with previous researches [ 11 , 43 ].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…All pruritic behaviors were evaluated as previously described with minor modifications [ 6 , 43 , 44 ]. The tests of algogenic behavior by capsaicin were performed similar with previous researches [ 11 , 43 ].…”
Section: Methodsmentioning
confidence: 98%
“…It is well-known that GRPR-positive neurons in the spinal cord constitute a long-sought labeled line for itch not pain sensation [ 10 ]. In our previous research, the results of proton nuclear magnetic resonance ( 1 H-NMR) studies of the spinal cord extracts revealed that the metabolites showed very different patterns for pruritogen and algogenic substance [ 11 ]. Given the high prevalence of itch in some patients with skin diseases [ 12 14 ], it is pivotal to know whether the genes are dysregulated in the spinal cord in different itch models.…”
Section: Introductionmentioning
confidence: 99%
“…For the study of metabolites, the liver samples were extracted with the same protocol as our former studies [ 35 , 36 ]. Here the procedure was briefly described.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid advancements in high-throughput technologies and computational frameworks offer an excellent opportunity to quantify spinal nociception using neuronal activation induced by noxious stimuli. The author's previous study showed that transcriptomics and metabolomics enable the examination of spinal biological systems in unprecedented detail (32)(33)(34)(35)(36). More recently, different patterns were revealed in the metabolic and transcriptional levels of the thoracic spinal cord under myocardial ischemia-reperfusion injury (37)(38)(39).…”
Section: Quantitative Proteomics Reveal the Alterations In The Spinalmentioning
confidence: 99%